Digestibility of diets containing Enertia s/f® and soybean oil in equines and effect of cobalt chloride on fermentation of alfalfa and smooth bromegrass hay by equine cecal microorganisms - Fehlberg, Laura Kay (Kansas State University, 2018)
Supplementation of lipids in the form of triglycerides is a safe method for increasing energy density in equine diets; however the effects of calcium salts of fatty acids (CSFA) on nutrient digestibilities in the horse are unknown. Eight cecally cannulated Quarter Horses were utilized in a crossover design in which horses consumed 1.5% BW smooth bromegrass hay and 0.5% BW concentrate supplemented with 4.1% soybean oil (SB) or 4.9% Enertia s/f® (E), a proprietary CSFA, for 28 d. Feces were collected for determination of apparent total tract digestibility of nutrients, and cecal digesta was evaluated for pH and concentrations of VFA and LCFA. Serum was collected following a 16-h fast and analyzed for triglycerides and cholesterol. Apparent total tract digestibilities of DM, NDF, ADF, CP, ether extract, and GE were unaffected by lipid source (P > 0.10). Serum triglycerides tended to be greater in horses consuming E compared to SB (P = 0.10); but, serum cholesterol concentrations were not different (P = 0.45). Cecal pH was unaffected by lipid source. Cecal concentration of total VFA tended to be greater in horses consuming SB compared to E at 2-h post feeding (P = 0.07). Cecal propionate concentrations were greater at 2-h post feeding for horses fed SB compared to horses fed E (P = 0.03). A treatment × time interaction was detected for total cecal LCFA concentration in which total cecal LCFA were greater in horses consuming E compared to SB at 2-h following consumption of a meal but became more similar as time progressed (P < 0.01). Secondly, an in vitro study was conducted to determine the effect of Co chloride on fermentation parameters using an equine cecal fluid inoculum in a 2 × 5 factorial arrangement of treatments. Alfalfa or smooth bromegrass hay (5 g DM) were utilized as substrates and were supplemented with 0.0, 0.5, 5.0, 25.0, or 50.0 mg Co/kg substrate DM. Cultures containing alfalfa had greater IVDMD compared to those with smooth bromegrass hay (P < 0.01). There was a forage × Co interaction in which gas production increased with time and was greater in cultures containing alfalfa (P < 0.01). Production of acetate, propionate, butyrate, isobutyrate, isovalerate, and total VFA, as well as acetate:propionate, were increased in cultures containing alfalfa compared to those containing brome hay (P < 0.05).
Keywords: Lipid; Digestibility; Cobalt; Calcium salts of fatty acids